A SCIENTIFIC EVALUATION OF AYURVEDIC DRUGS IN THE MANAGEMENT OF DIABETES MELLITUS TYPE 2: AN EVIDENCE BASED REVIEW - Garg, *Richa; Kamal, Sachdev; Dharmendra, Dr. (International Journal of Ayurveda and Pharma Research, 2017)
Diabetes Mellitus (DM) is a major challenging health problem of the 21st century. Prevalence of DM is rapidly rising throughout the globe where India leads with largest number of diabetics and became â€œDiabetes capital of the worldâ€. It refers to a heterogenous chronic metabolic disorder that shares the phenotype of hyperglycaemia. DM is caused by a complex interaction of genetic, behavioural and environmental factors. It results due to impaired insulin secretion or insulin resistance, decreased glucose utilization and increased glucose production. It is characterized by polyuria, polydipsia, weight loss, fatigue, Dryness of mouth and throat, constipation and instance itching. Diabetes mellitus is of two types- Type I - IDDM (Jata pramehi or Sahajapramehi) Type II - NIDDM (Sthula pramehi and Apathyanimittaja pramehi).Ayurvedic management strategy of Apathayanimittajaprameha (type-2 diabetes mellitus) include Snehana (oleation), Shodhan and shaman treatments accompanied with suitable dietary and life style modification which has been found very effective. In Ayurvedic system of medicine various single herbs, herbal formulations, herbominerals and minerals are using popularly and very effectively in the treatment of Madhumeha i.e., Diabetes Mellitus type- 2. Many Ayurvedic drugs revalidated to having anti-diabetic and anti-hyperglycaemic activity by clinical and experimental study but many are awaited. In this study, the initiation have been taken to collect and compiled all the related information regarding Ayurvedic drugs used therapeutically that may facilitate further research works.